Overview Of Umkm Taxpayer Compliance UMKM Cases In Aceh Province - Cut Tara Merinda; Rita Meutia; Indayani Indayani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of tax socialization, taxpayer awareness and tax knowledge on MSME taxpayer compliance in the Districts/Cities of Aceh Province. The population of this study is all MSMEs registered in the Aceh Regional Office of the Directorate General of Taxes. While the determination of the number of samples in this study using the Slovin formula and obtained the results of 397 respondents consisting of 23 Districts/Cities in Aceh Province. Data collection techniques used in this study were to use a questionnaire and data analysis methods using multiple linier regression with analysis tools using SPSS version 25. The results of this study indicate that simultaneously and partially variables of tax socialization, taxpayer awareness and tax knowledge affect taxpayer compliance.